The Impact Of Workload on Nurse Burnout In The Hospital - Desti Puswati; Titin Wahyunani (HEALTH CARE: JURNAL KESEHATAN, 2025)
Background: Nurses frequently report experiencing professional burnout in the workplace; however, quantitative evidence regarding the contributing factors is currently lacking within the Inpatient Department of Arifin Achmad Regional General Hospital, Riau, Indonesia. Therefore, this study aimed to examine the impact of workload on nurse burnout in this specific setting. Objectives: The primary objective of this study was to examine the relationship between workload and nurse burnout among nurses working in the Dahlia and Edelweis wards of Arifin Achmad Regional General Hospital, Riau, Indonesia. Methods: This study utilized a quantitative correlational design with a cross-sectional approach. The research was conducted in the Dahlia and Edelweis wards of Arifin Achmad Regional General Hospital, Riau Province. The total sample size was 52 nurses, recruited using a total sampling technique. Data collection instruments were adapted from Nursalam (2015). The research period spanned from September 2024 to February 2025.  Results: The study demonstrated a statistically significant relationship between workload and nurse burnout among the nurses at Arifin Achmad Regional General Hospital. This finding is supported by the high prevalence rates observed for both heavy workload (71.2%) and severe burnout (65.4%). Conclusion: This finding aligns with existing literature, affirming that workload is a major determinant of burnout among nursing staff. The results strongly suggest that high workload contributes to the critical level of burnout observed in the Inpatient Department.